Environmental determinants of Opisthorchis viverrini prevalence in northeast Thailand - Yi-Chen Wang; Chen-Chieh Feng; Paiboon Sithithaworn (Geospatial Health, 2013)
Opisthorchis viverrini infection is an important, human, parasitic disease along the middle and lower Mekong River of Southeast Asia. Despite vast efforts in epidemiological research, the wide geographical variation in O. viverrini prevalence remains unexplained. To investigate the potential influence of village location, prevalence data recorded during the year 2009 for 90 villages in northeast Thailand were analysed by a geographical information systems approach based on a digital elevation model for altitude determination. Land use compositions of village surroundings were derived from images produced by the Thematic Mapper of the Landsat satellite and landscape metrics were applied to quantify spatial patterns. Pearson’s correlation coefficients were used to evaluate the associations between the environmental factors and O. viverrini prevalence. In spite of no statistical difference (P = 0.117), higher-ground villages generally had a lower level of opisthorchiasis than those situated lower down, while a significant negative correlation was detected between O. viverrini prevalence and the composition of farmland with low water content (P = 0.028), indicating the potential influence of agricultural lands with drought-tolerant crops. Strengthening this hypothesis, a significant positive association with O. viverrini prevalence was found for the combined land use classes of water and of farmland with high water content (P = 0.032), indicating that the dominance of a large land use patch capable of providing suitable habitats for the intermediate hosts might contribute to the disease. This study highlights the influence of landscapes on the epidemiology of O. viverrini infection and emphasises the need to incorporate land use planning into control strategies.